スウチ ケイサン ニ ヨル ヒガシ ナンキョク シラセ ヒョウガ リュウイキ ヒョウショウ ノ 10000 ネン ゴ ノ ヒョウショウ ヘイコウ ケイ ノ ミツモリ - 藤田, 秀二; フジタ, シュウジ; 池田, 範和; イケダ, ノリカズ; 東, 信彦; アズマ, ノブヒコ; 本堂, 武夫; ホンドウ, タケオ; 前, 晋爾; マエ, シンジ; Fujita, Shuji; Ikeda, Norikazu; et al. (1991)
P(論文) 東南極, 白瀬氷河流域では, 近年の観測により氷床表面高度の低下が観測されている。この変動を氷床が近年の気候に適合していく過程としてとらえるならば, 現在の気候に対応する氷床の平衡形を求めれば, 現在の氷床の挙動を理解できる手がかりが得られる。三次元非定常氷床流動モデルを用いて, 氷床の平衡形が見積もられた。モデル計算には, 基盤地形, 表面涵養量, 氷床表面高度, 氷床表面温度について, 観測値とその外挿値を用いた。そして, 氷床表面温度, 表面涵養量, 地殻熱流量などのパラメーターを様々に変えた場合の氷床の形を求めた。計算の結果, 計算を現在の氷床形から開始した場合(10)^4年後までの計算で氷床は平衡形に達した。平衡形は, テストしたパラメーターに大きく依存するが, 一般的傾向としては氷厚は中流域で低下し下流域で増大する。やまと山脈近傍ではパラメーターの値を変えても氷床の変動は比較的小さいことが示された。 Recent observations show that the ice sheet in the Shirase Glacier drainage basin, East Antarctica, is thinning. If the observed thinning is assumed to be a transitional process in which the ice sheet is adjusting to the present climate, an equilibrium ice sheet profile which adjusts to the present climate would provide us with information for understanding the present behavior of the ice sheet. The equilibrium ice sheet profile was estimated by using a three-dimensional non-steady state ice sheet model. Estimations were carried out with data based on observations of bedrock topography, surface elevation, accumulation rate and surface temperatures, and their extrapolation for areas where there is no field data. And the equilibrium ice sheet profile against various parameters, e.g. surface temperatures, accumulation rate and geothermal heat flux, was investigated. Results of the calculation showed that an almost stationary state of the ice sheet was achieved after (10)^4 model years when started from the present profile of the ice sheet. The equilibrium ice sheet profile depended on bedrock topography and tested parameters sensitively, but the calculations indicated that ice-thickness tend to decrease in the middle-stream region in general. It was also revealed that the ice sheet in the vicinity of the Yamato Mountains was relatively stable even if the parameters were changed. departmental bulletin paper